Fungsi Implikatur dalam Tuturan Najwa Shihab di Acara ‘Gelar Wicara Mata Najwa’ Episode “Menangkal Corona dan Menanti Terawan” - Tessa Qurrata Aini; Ike Revita; Aslinda Aslinda (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to identify the functions of implicatures foung in Najwa Shihab’s utterances in ‘Mata Najwa Talk Show’ of episodes of “Against Corona and Waiting for Terawan.” This study uses a descriptive method with a qualitative approach due to its data in the form of implicature function of utterances that as it is. There are 353 data which downloaded from the YouTube videos of “Against Corona and Waiting for Terawan.” Data were collected using the listening method or usually known as non-participant observation method. Data analysis used pragmatic matching method and sorting technique (PUP) with referential sorting power technique and comparison and differentiation technique (HBB). Research results are presented through formal and informal methods with descriptive explanation and using tables and diagrams. The results of the research indicate that there are three implicature functions used in Najwa Shihab’s utterances in in ‘Mata Najwa Talk Show’ of episodes of “Against Corona and Waiting for Terawan”: (1) assertive/representative function, (2) directive function, and (3) expressive function. The most often used of implicature function found in this study is the directive function. This is due to the fact that Shihab’s speech has many implicatures that function to ask and order her listeners. Shihab as the presenter of the talk show usually asks the resource person related to the topic. In addition, Shihab also requests the audience to do something in order to direct the talk show smoothly and communicatively.